Emerging technologies, novel crimes, and security: the good, the bad, and the ugly - Nasheri, Hedieh (Routledge, 2025)
"This book provides a holistic overview of the complexities of modern technological advances and their implications for crime and security. It examines the societal dilemmas that accompany these technologies, their strategic impact on geopolitics, governments, business, and civil society. The increasingly interconnected world gives rise to novel crimes and creates a new, complex set of threats. Understanding this landscape is essential to strategizing for the prevention, protection, mitigation, and risk assessment of technology-related crime. Practical and approachable, this book builds knowledge and awareness of the impact of emerging technologies on crime and security among professionals, students, academicians, researchers, and policymakers"--